A Social Audit Model for Agro-biotechnology Initiatives in Developing Countries: Accounting for Ethical, Social, Cultural, and Commercialization Issues - Obidimma Ezezika; Fiona Thomas; Abdallah Daar; Peter Singer (Journal of Technology Management & Innovation, 2009)
There is skepticism and resistance to innovations associated with agro-biotechnology projects, leading to the possibility of failure. The source of the skepticism is complex, but partly traceable to how local communities view genetically engineered crops, public perception on the technology’s implications, and views on the role of the private sector in public health and agriculture, especially in the developing world. We posit that a governance and management model in which ethical, social, cultural, and commercialization issues are accounted for and addressed is important in mitigating risk of project failure and improving the appropriate adoption of agro-biotechnology in sub-Saharan Africa. We introduce a social audit model, which we term Ethical, Social, Cultural and Commercialization (ESC2) auditing and which we developed based on feedback from a number of stakeholders. We lay the foundation for its importance in agro-biotechnology development projects and show how the model can be applied to projects run by Public Private Partnerships. We argue that the implementation of the audit model can help to build public trust through facilitating project accountability and transparency. The model also provides evidence on how ESC2 issues are perceived by various stakeholders, which enables project managers to effectively monitor and improve project performance. Although this model was specifically designed for agro-biotechnology initiatives, we show how it can also be applied to other development projects.